Perilaku Merokok Pada Anak - Setyawati, Dyahningrum (2016)
ABSTRACT The Phenomena of smoking behavior is worrying , not only for adults for teenagers , this habit now become a trend for children. The aim of this research is to know smoking behavior on the childrens at age 6 up to 12 years old, where at this age the most important in children development is have good socializing with friens or surroundings. The subject of this research are 6 elementary school students in Sekaran village. This research uses qualitative methods with descriptive approach. Researcher uses interviews and observation method to collect data and uses content analysis to analize data. The result of the reasearch shows that children smoking behavior begin at age 5 until 9 in average. They did it behavior alone or together with friends in a quite place, such as school, home, river, field, rice field, graveyard, and their neighbor's garden. They felt bitter when they smoke for the first time, they cough, but they still did it because they felt enjoy when they come together in a place and smoking together. They addicted, and then they felt enjoy, sweet, or cool. There were two factors influences this habit, they're internal and external factors. Internal factors are included self-pretension, less of self-control, and less of education about smoking behavior. Eksternal factors are parents or friends modelling, friends challenge, friends order, less of parents control, and easy acces to get cigarette. They felt happy, peaceful, satisfied, and had impressive felling when smoking together. Smoking behavior have some negatif impact, they're suscibtible to cough or easy to felt tired, and have a painful in their chest.